CDR 2019
DOI: 10.20517/cdr.2019.66
|View full text |Cite
|
Sign up to set email alerts
|

RET in breast cancer: pathogenic implications and mechanisms of drug resistance

Abstract: Initiation, progression, outcome and sensibility to therapies in breast cancer (BC), the most frequent cancer in women, are driven by somatic and germline mutations. Although the effectiveness of hormonal therapies is well-founded, it is prescribed for cancers which express steroid hormone receptors, such as estrogen receptor (ER). RET is a protooncogene encoding a transmembrane tyrosine kinase receptor that is activated by one of its four ligands (GDNF, neurturin, artemin or persephin) and one of its corecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 137 publications
1
12
0
Order By: Relevance
“… 54 In addition to its involvement in the initiation and progression of breast cancer, 55 studies found that RET was associated with resistance to endocrine therapy. 56 Our results are consistent with the effects of RET in promoting cancer cell proliferation and invasion, as patients with high RET expression demonstrated shorter PFS.…”
Section: Discussionsupporting
confidence: 88%
“… 54 In addition to its involvement in the initiation and progression of breast cancer, 55 studies found that RET was associated with resistance to endocrine therapy. 56 Our results are consistent with the effects of RET in promoting cancer cell proliferation and invasion, as patients with high RET expression demonstrated shorter PFS.…”
Section: Discussionsupporting
confidence: 88%
“…S4; ref. 28 ). As a comparison, the WHIM9 PDX line, which expresses WT ERα and showed partial sensitivity to E2 deprivation ( 7 ) has a relatively low level of RET (lower 50% percentile), but the expression of RET mRNA and protein was highly E2 induced (upper 25% percentile), as expected, given that RET is directly transcriptionally regulated by ERα ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RET amplification is the most common, followed by RET fusion. Most RET mutations in BC appear after drug resistance, and CCDC6-RET and NCOA4-RET occur frequently ( 50 ). RET is actionable in ER + BC.…”
Section: Ret Gene and Tumor Occurrencementioning
confidence: 99%